Effects of postimplantation systemic inflammatory response on long-term clinical outcomes after endovascular aneurysm repair of an abdominal aortic aneurysm. Issue 32 (August 2016) - Kwon, Hyunwook; Ko, Gi-Young; Kim, Min-Ju; Han, Youngjin; Noh, Minsu; Kwon, Tae-Won; Cho, Yong-Pil
Abstract : Abstract: The aim of this study was to determine the association between postimplantation syndrome (PIS) and long-term clinical outcomes after elective endovascular aneurysm repair (EVAR) of an abdominal aortic aneurysm. In this single-center, observational cohort study, a total of 204 consecutive patients undergoing EVAR were included. Primary outcome was long-term mortality from any cause; secondary outcomes included long-term mortality, systemic or implant-related complications, and secondary therapeutic procedures. The diagnosis of PIS was established in 64 patients (31.4%). PIS patients were more likely to receive woven polyester endografts and have a longer postoperative hospital stay and lower incidence of type II endoleaks. In multivariate analysis, PIS was significantly associated with a decreased risk of developing type II endoleaks ( P = 0.044). During follow-up period of 44 months, clinical outcomes showed no significant differences in mortality ( P = 0.876), systemic ( P = 0.668), or implant-related complications ( P = 0.847), although rates of secondary therapeutic procedure were significantly higher in non-PIS patients ( P = 0.037). The groups had similar rates of overall survival ( P = 0.761) and other clinical outcomes ( P = 0.562). Patients with and without PIS had similar long-term overall survival rates and other clinical outcomes. PIS was beneficial in preventing type II endoleaks during postoperative period.